2008
DOI: 10.1007/s00431-008-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

Airway clearance techniques to treat acute respiratory disorders in previously healthy children: where is the evidence?

Abstract: Airway clearance techniques are an important part of the respiratory management in children with cystic fibrosis, bronchiectasis and neuromuscular disease. They are also, however, frequently prescribed in previously healthy children with an acute respiratory problem with the aim to speed up recovery. The current review explores the evidence behind this use of airway clearance techniques in children without underlying disease. Few studies have been performed; many different techniques are available and the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…[30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended. [35][36][37] In France, increased-exhalation technique has been widely used in various ways since the 1970s. [38][39][40] A robust thoraco-abdominal pressure is applied to mimic the forced expiratory technique.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…[30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended. [35][36][37] In France, increased-exhalation technique has been widely used in various ways since the 1970s. [38][39][40] A robust thoraco-abdominal pressure is applied to mimic the forced expiratory technique.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…CPT has been used as an adjunct to decrease severity, length of illness, and improve outcomes of this serious disease. However, De Boeck and colleagues 73 found little evidence to support use of CPT to treat pneumonia. Studies that supported the use of CPT to treat pneumonia did not have well-defined inclusion criteria and were published in the 1980s.…”
Section: Review Of Current Evidencementioning
confidence: 99%
“…Studies have not demonstrated improvement in signs and symptoms, decreased length of illness, decreased LOS, 75,76 or reduction in duration of fever. 73 Furthermore, pneumonia occurs in the peripheral airways; therefore, secretions are not located in an area where CPT could facilitate movement of secretions out of the airways. 73,74 In a Cochrane database review, Chaves et al 77 looked at CPT in the treatment of pneumonia in which the primary outcome criteria were mortality, LOS, and time to clinical resolution.…”
Section: Review Of Current Evidencementioning
confidence: 99%
See 2 more Smart Citations